Primary hepatic origin of a neuroendocrine tumor: A rare case report. (December 2022) - Bouzayan, Laila; Madani, Ayoub; Malki, Samia; Abbou, Widad; Skiker, Imane; Benani, Amal; Jabi, Rachid; Bouziane, Mohammed
Abstract: Introduction: Neuroendocrine tumors are mainly located in gastrointestinal tract, pancreas and lungs. The primary hepatic origin of neuroendocrine tumors is extremely rare. Case presentation: A 57-year-old female with a history of cholecystectomy presented to our hospital for right upper abdominal pain lasting for 2 months. Abdominal computed tomography revealed a large exophytic soft-tissue mass in the left liver lobe. Tumor markers were within the normal range. Octreoscan confirmed the primary hepatic origin of neuroendocrine tumor. The patient underwent left hepatic resection. Pathological and immunohistochemical examination of the resected specimen showed a well-differentiated grade 2 neuroendocrine tumor. Clinical discussion: Primary hepatic neuroendocrine tumors represent rare hepatic tumors. These tumors may occur at any age with an average of 50 years. Diagnosis algorithm includes two key steps: firstly, the confirmation of the endocrine nature of the tumor and secondly the confirmation of its primary nature. Conclusion: Neuroendocrine tumors are a very rare entity. The primary hepatic location is exceptional. The diagnosis is based on pathological and immunohistochemical examination as well as the result of the octreoscan. Highlights: The primary hepatic origin of neuroendocrine tumors is extremely rare.